Time-lapse imaging of alveologenesis in mouse precision-cut lung slices - Akram,K; Yates,L; Mongey,R; Rothery,S; Gaboriau,D; Sanderson,J; Hind,M; Griffiths,M; Dean,C (Bio-protocol, 2019)
Alveoli are the gas-exchange units of lung. The process of alveolar development,alveologenesis, is regulated by a complex network of signaling pathways that act on various cell typesincluding alveolar type I and II epithelial cells, fibroblasts and the vascular endothelium. Dysregulatedalveologenesis results in bronchopulmonary dysplasia in neonates and in adults, disrupted alveolarregeneration is associated with chronic lung diseases including COPD and pulmonary fibrosis.Therefore, visualizing alveologenesis is critical to understand lung homeostasis and for thedevelopment of effective therapies for incurable lung diseases. We have developed a technique tovisualize alveologenesis in real-time using a combination of widefield microscopy and imagedeconvolution of precision-cut lung slices. Here, we describe this live imaging technique in step-by-stepdetail. This time-lapse imaging technique can be used to capture the dynamics of individual cells withintissue slices over a long time period (up to 16 h), with minimal loss of fluorescence or cell toxicity.